The Impact of Matching Mission Preferences on Well-being at Work - Robin Zoutenbier (Tinbergen Institute, 2014)
A recent literature in economics assumes that workers differ in their mission preferences. These studies predict a premium on the matching of mission preferences between a worker and employer. This paper uses data from the Dutch LISS panel to examine this prediction for government workers. Results show that government workers whose political preferences match those of the political parties in office are more satisfied with the type of work they do as compared to government workers whose political preferences do not match. A match of political preferences has no effect on the job satisfaction of workers outside the government sector.
Keywords: H1; J45; M5; 330; job satisfaction; mission motivation; public sector; bureaucrats